Unrestricted market access for Sub-Saharan Africa : how much is it worth and who pays - Ianchovichina, Elena 2000- (Policy research working paper, 2001)
The European Union, Japan and the United States have recently announced initiatives to improve market access for the poorest countries. How would these initiatives affect Sub-Saharan Africa and the rest of the world